The Role of Community Participation in Supporting Tomohon City Regional Regulation No. 1 of 2021 - Rahman Dilapanga, Abdul; Fransisco Supit, Brain; Mandagi, Anastasya K. V. (Indonesian Association for Public Administration (IAPA), 2023)
This research aims to evaluate community participation in efforts to support the Regional Regulation of Tomohon City No. 1 of 2021 concerning Increasing Discipline and Law Enforcement of Health Protocols in Preventing and Controlling Covid-19. This study uses a qualitative method. The research results show that Regional Regulation of Tomohon City no. 1 of 2021 has been implemented well by the government in terms of socialization, implementation and supervision. However, community participation is still relatively low. In fact, the city of Tomohon is often included in the red zone for the spread of the Covid-19 outbreak. This proves that the level of community participation is relatively low. The influencing factors are 1) lack of understanding and awareness, 2) spread of incorrect information (hoaxes), 3) distrust of the government, 4) pandemic fatigue, 5) social and economic factors.